Effect of silver diamine fluoride/potassium iodide treatment on the prevention of dental erosion in primary teeth: an in vitro study - Lamia Khairy Gadallah; Engie Mohamed Safwat; Reham Sayed Saleh; Shereen Musa Azab; Maha Moussa Azab (Nature Publishing Group, 2023)
Abstract Introduction Dental erosion has a great effect on oral health, when diagnosed it is irreversible, this sets the importance of different preventive measures being investigated against dental erosion. Aim This in vitro study aims to evaluate the effectiveness of silver diamine fluoride and Potassium iodide (SDF-KI) in comparison to casein phosphopeptide-amorphous calcium phosphate fluoride (CPP-ACPF) varnish, sodium fluoride (NaF) varnish, silver diamine fluoride (SDF) alone and deionized water as a control group in the prevention of dental erosion in primary teeth and assessing its staining effect. Materials and methods Forty deciduous teeth enamel specimens were randomly allocated into the five study groups. Tested materials were applied. An erosive challenge was done by immersing the specimens in a citric acid-containing soft drink with pH 2.85, for 5 min, 4 times/day, for 5 days. Changes in surface microhardness, mineral loss, and color change were evaluated besides recording of the surface topography and surface roughness for selected specimens. Results The highest decrease in surface microhardness was recorded in the control group (−85.21 ± 10.60%), with a statistically significant difference (p = 0.002). SDF-KI group (−61.49 ± 21.08%) showed no statistically significant difference when compared to CPP-ACPF, NaF, and SDF groups. For calcium and phosphorous loss, control group was statistically significantly higher compared to the treatment groups (p = 0.003) and (p < 0.001) respectively, while there was no statistically significant difference between the tested treatment groups. The highest mean value for color change was recorded in SDF group (26.26 ± 10.31), followed by SDF-KI group (21.22 ± 12.87) with no statistically significant difference between groups. Conclusions SDF-KI is as effective as CPP-ACPF, NaF varnishes and SDF in the prevention of dental erosion in primary teeth, there was no statistically significant difference regarding its staining potential.